Accretion and star formation in quasars - White, S (2015)
Studying the interplay of accretion and star formation is crucial to our understanding of galaxy evolution. The new generation of radio surveys are able to play a key role in this area, since both processes produce radio emission. As we probe low radio-luminosities, the two main populations are star-forming galaxies and radio-quiet quasars (RQQs). How they contribute to the total radio emission is under debate, with previous authors arguing that star formation dominates. In this thesis I investigate the relative levels of radio emission due to accretion and star formation in RQQs. Firstly, I select a sample of 74 quasars from the VISTA Deep Extragalactic Observations (VIDEO) survey, whose depth allows me to study very low accretion rates and/or lower-mass black holes. By comparing radio emission from the quasars with that from a control sample of galaxies, and calculating two independent estimates of star-formation rate, I show that this emission is predominantly related to the accretion process. A second sample of 72 RQQs is obtained from the Spitzer-Herschel Active Galaxy Survey, spanning a factor of ∼100 in optical luminosity over a narrow redshift range at z∼1. This enables evolutionary effects to be decoupled when comparisons are made with the VIDEO sample. I reduce radio data from the Karl G. Jansky Very Large Array (JVLA) for these objects, and find further support that accretion makes a significant contribution to the radio emission in RQQs. In addition, the levels of accretion and star formation appear to be weakly correlated with each other, and with optical luminosity. These findings offer an insight into how the mechanisms behind galaxy evolution may interact differently in RQQs compared to their radio-loud counterparts. They also have important implications for modelling radio populations below 1mJy, which is necessary for the development of the Square Kilometre Array.